Pengaruh Profitabilitas, Struktur Modal, Dan Likuiditas Terhadap Nilai Perusahaan Pada SektorFarmasi Yang Terdafatar Di Bursa Efek Indonesia 2018 – 2021 - Sinaga, Krismes; Ramadani, Apriansyah; Adinda (JEBIM Prima, 2023)
Pharmaceutical companies or drug companies are commercial business companies that focus on researching, developing and distributing drugs, especially in health matters. They can make generic drugs or brand name drugs. This research uses quantitative methods, quantitative methods are research based on the philosophy of positivism, used to examine certain populations and samples. This study used 20 samples from pharmaceutical companies listed on the IDX for the period 2018 – 2021. The results of this study indicate that the profitability variable on company value has a value of 0.060 > 0.05 and a Tcount value of 2.025 > Ttable 2.131. So it canbe concluded that profitability partially has a positive but not significant effect on firm value.The Sig value for influencing the capital structure on firm value is 0.004 <0.05 and the Tcount value is 3,381 > Ttable 2,131. So it can be concluded that the capital structure partially has a positive and significant effect on firm value. The Sig value for influencing liquidity on firm value is 0.161 > 0.05 and the Tcount value is 1,470 <Ttable 2,131. So it can be concluded that liquidity has a positive but not significant effect on firm value. And based on the value of Fcount 5.775 > from Ftable 3.24 it indicates that the results of the study accept H4 which means that there is an influence on profitability, capital structure, and liquidity which simultaneously has a positive and significant effect on firm value.